2008
DOI: 10.1021/jf8026217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Wine Pomace Extract and Oleanolic Acid on Plasma Lipids in Rats Fed High-Fat Diet and Its DNA Microarray Analysis

Abstract: The aim of this study was to evaluate the concentration of oleanolic acids (OA) in pomace, a winemaking byproduct, and its influence on the levels of plasma lipids in rats fed a high-fat diet and on hepatic gene expression using DNA microarray analysis in vivo. HPLC analyses of pomace ethanol extract (PEE) revealed a high amount of OA ranging from 4 to 11 g/100 g. Male Sprague-Dawley rats were fed a normal-fat diet (NF group), a high-fat diet with 21% lard (HF group), a high-fat diet with 0.05% OA (OA group, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 43 publications
4
48
0
1
Order By: Relevance
“…3). This corresponds to previous findings that have shown that the presence of OA in raisins is independent of whether the grapevine cultivar is red or white (Orbán et al, 2009;Yunoki et al, 2008). We were unable to confirm the reasons for the differences in OA content between the different raisin types in this study, as the OA content in the raw materials and any changes that occurred during manufacture were unknown.…”
Section: Resultssupporting
confidence: 64%
“…3). This corresponds to previous findings that have shown that the presence of OA in raisins is independent of whether the grapevine cultivar is red or white (Orbán et al, 2009;Yunoki et al, 2008). We were unable to confirm the reasons for the differences in OA content between the different raisin types in this study, as the OA content in the raw materials and any changes that occurred during manufacture were unknown.…”
Section: Resultssupporting
confidence: 64%
“…Methanol extract yields obtained by the maceration and Soxhlet methods were 7% and 8.2%, respectively (g/100 g of dry weight). Extraction yields from white and red grape pomace have been reported in the range of 7-37% (Yunoki et al, 2008). The quality of grape pomace extract is due to both its yield and its phenolic content.…”
Section: Extractsmentioning
confidence: 99%
“…Similar observations were made in mice fed resveratrol (0.4%) for 15 weeks, 25 grape seed extract (250 mg/kg bw) for 12 weeks, 5 and dietary wine pomace extract (0.45%) for 4 weeks. 17 Feeding mice with HF diet increased the weight of epididymal adipose tissue by 67% compared to the fat mass in their lean counterparts on LF diets (Table 3). Supplementation of MGP and MWP in the HF diet significantly reduced fat mass by 29 and 12.5%, respectively, as compared to the HF group.…”
Section: Food Intake and Body And Tissue Weights In Micementioning
confidence: 99%